Luminescent sensing of nitroaromatics by crystalline porous materials - Dutta, Archisman; Singh, Amita; Wang, Xiaoxiong; Kumar, Abhinav; Liu, Jianqiang (CrystEngComm, 2020)
Porous crystalline materials (PCMs) constitute a class of covalent or supramolecular coordination architectures having intensive application in the fields of sensing, gas separation and storage, catalysis and optoelectronic device engineering. The theoretical investigations on these porous crystalline systems using multiple wave functions add fundamental insights into better understanding of highly selective sensing. A lot of recent reports focus on various archetypal luminescent porous organic frameworks, like metal organic frameworks (MOFs), covalent organic frameworks (COFs), or nanocomposites having excellent luminescence sensing performance against a plethora of nitroaromatic compounds and explosives. These exceptional classes of compounds display unique characteristic photochromism and electronic properties which can be tuned from the grass-root level by modifying metal-ligand interactions and various supramolecular interactions at the molecular level. Thus, developing luminescent porous organic frameworks having ultra-fast capacity of sensing nitroaromatic compounds and explosives reversibly with high selectivity and low limits of detection (LOD) is urgently required for national security, as well as homeland and environment safety. The reusability of these porous frameworks can only be anticipated if the crystallinity of these materials is retained after repeated use followed by construction of these frameworks with cheaper starting materials. The present review mainly encompasses the recent progress in various luminescent PCMs incorporating transition metals, lanthanides, nanocomposites, and main group elements having sensing technology applications along with the theoretical insights and possible mechanisms behind " turn-on " or " turn-off " luminescence. Designing strategies for the syntheses of targeted luminescent MOFs, nanoparticle/MOF composites and COFs described and their application in sensing nitroaromatic compounds and explosives discussed.